Evaluation and Early Warning Simulation of Personnel Unsafe Behavior in Mines Prone to Coal-Rock Dynamic Disasters - Jueli Yin; Huiying Chen; Zhen Liu; Linchao Shi; Kai Yu; Biao Kong (Geofluids)
At present, aging mines are faced with development bottlenecks such as lack of national policy support, serious problems left over from history, and difficulties in enterprise transformation and development, which seriously restrict the safe production and sustainable development of aging mines. In order to deeply analyze the influencing factors of group unsafe behavior in aging mines, the evolution law of unsafe behavior is qualitatively simulated and quantitatively analyzed to realize the safety evaluation of group unsafe behavior in aging mines. Based on this analysis of the emergence mechanism and influencing factors of unsafe behavior in aging mines, the evaluation index of unsafe behavior in the aging mine population was established. These include six criterion layers and 30 index layers; the mutation level value of the target layer is 0.9405. Group dynamic effect and safety management factors are the two important factors restricting their development and safety. The unsafe behavior of the aging mine groups was evaluated based on game theory and system dynamics—dynamic game simulation on the influence of unsafe behavior in aging coal mines. A qualitative simulation analysis was also performed using the QSIM algorithm. The evolution law of the safety psychology and behavior of aging mine workers are analyzed. This paper shows the importance of the unsafe behavior of aging mines, which helps the safety production and clarifies the safety psychology and the behavior evolution law. This paper puts forward new methods and theories on the safety psychology and behavior evolution law of the safety behavior and provides a reference for the sustainable development of aging mines.